Aggressive Reporting and Probabilistic Auditing in a Principles-Based Environment - Suzanne H. Bijkerk; Vladimir A. Karamychev; Otto H. Swank (Tinbergen Institute, 2013)
We analyze the reporting strategies of firms and the investigation strategies of auditors in an archetype principles-based financial reporting system. To this end, we add a verification stage to a standard cheap-talk game, and apply the resulting game to financial reporting. We show that for a principles-based system to work properly, firms should bear a sufficient share of the cost of a thorough investigation. Furthermore, we find that a principles-based system is a mixed blessing. On the one hand, it leads to a plausible investigation strategy of the auditor, in which suspected reports receive most attention. On the other hand, a principles-based system only indirectly weakens firms' incentives to report aggressively.
Keywords: D82; M42; 330; Cheap Talk; Financial Reporting; Principles-based Regulation; Stochastic Auditing